Addressing the problem of reflexivity in theories of reflexive modernisation: Subjectivity and structural contradiction. (December 2015) - Farrugia, David
This article addresses debates within theories of reflexive modernisation about the meaning of reflexivity for understanding contemporary subjectivities. The article demonstrates that the contribution that this concept could make to theories of modern subjectivity has been limited by the problematic assumption that reflexivity describes a form of critical rationality leading to emancipation from social constraint and the sovereign self-fashioning of identity. Both critiqued and defended on these grounds, debate about reflexivity and reflexive modernisation has been limited by a sociologically unsustainable vision of modern subjectivity, and has left theories of reflexive modernisation open to the accusation that they are blind to the relationship between subjectivity and social structure. In response, this article constructs a theory of reflexivity as a social practice which reflects the contradictions and insecurities intrinsic to modern social structures. Conceived as a social practice, reflexivity is a concept that combines the macro and the micro, the structural and the personal. Capturing historically specific forms of structural organisation, as well as the practices through which these structures are made into biographies, the concept of reflexive subjectivity can make a significant theoretical contribution to understandings of modern identities.